Konsep Racang Ngi’is Sebagai Ritus Penanda Pendewasaan Perempuan dalam Budaya Suku Watong - Yohanes Jogo; Yosep Wilfridus Waso; Yulius Angelus Kogha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The Racang Ngi’is tradition is a distinctive feature of the Nagekeo community in general and the Watong tribe in particular. This tradition marks the coming of age of Watong women. Racang Ngi'is is also one of the cultural rites of the Watong tribe that still survives in this era of modernization. This study uses a qualitative approach with a literature study method and in-depth interviews with cultural figures of the Watong tribe. The purpose of this study is to explore and analyze the symbolic meaning of Racang Ngi'is and examine the concept of female maturation in the culture of the Watong tribe. It is believed that women who have undergone this process will become more independent and responsible. The results of this study show that the Racang Ngi'is tradition contains noble values that must be preserved and passed down from generation to generation. In addition to being known for its profound meaning in the development of women's maturity, this rite also has an important meaning for social life and spiritual development. Furthermore, women's dignity is valued in the stratification of Watong tribal society. Thus, this study concludes that the existence of the Racang Ngiis ritual must continue to be preserved from generation to generation.